2008
DOI: 10.1007/s12253-008-9027-y
|View full text |Cite
|
Sign up to set email alerts
|

No Strong Association Between HER-2/neu Protein Overexpression and Gene Amplification in High-grade Invasive Urothelial Carcinomas

Abstract: The generation of urothelial carcinoma is caused by the accumulation of various molecular changes, as in most malignancies. There are conflicting data about the status of HER-2/neu oncogene in urothelial carcinomas. The aim of this study was to determine the status of HER-2/neu oncogene in high-grade invasive urothelial carcinoma of urinary bladder both in protein and DNA level. We evaluated HER-2/neu protein overexpression by immunohistochemistry (IHC) and gene amplification by fluorescent in situ hybridizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
45
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 19 publications
(19 reference statements)
5
45
0
Order By: Relevance
“…Consistent with other published studies of HER2 immunohistochemical staining in urothelial carcinoma, 9,[12][13]15,20 we considered carcinomas positive if they exhibited 2 þ or 3 þ immunostaining.…”
Section: Immunohistochemistrymentioning
confidence: 67%
See 4 more Smart Citations
“…Consistent with other published studies of HER2 immunohistochemical staining in urothelial carcinoma, 9,[12][13]15,20 we considered carcinomas positive if they exhibited 2 þ or 3 þ immunostaining.…”
Section: Immunohistochemistrymentioning
confidence: 67%
“…37 As a result, studies have often found a 100% correlation between HER2 protein expression and aneusomy of chromosome 17. 12,30 However, the finding of HER2 gene amplification in a large proportion of our micropapillary carcinoma cases suggests an additional mechanism for HER2 protein expression in this urothelial carcinoma variant and suggests the potential relevance of HER2 in micropapillary carcinoma biology and therapy.…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations